Le strane vicende di mia vita: Il carteggio di Giuseppe De Blasiis The Strange Events of My Life: The Correspondence of Giuseppe De Blasiis - Antonella Venezia (Scuola delle Scienze Umane e Sociali. Quaderni, 2018)
This volume contains the correspondence of Giuseppe De Blasiis (1832-1914), the first History professor of the Neapolitan University. In his leading role as a 19th century Italian Historiographer, he was responsible for the scientific structure of the Neapolitan Society of National History, of which he was a founding member and later president. His studies on Medieval History, without forgetting those he carried out on the modern age, as well as his vast knowledge of the documentary and bibliographical sources from Naples, made him a privileged spokesman for anyone who wanted to approach the history of southern continental Italy.